IMPLEMENTASI MODEL PEMBELAJARAN VALUE CLARIFICATION TECHNIQUE (VCT) UNTUK MENINGKATKAN HASIL BELAJAR DAN SIKAP TOLERANSI SISWA SEKOLAH DASAR - Seran, Eliana Yunitha; Mardawani, Mardawani; GS, Agustina Sivianty (STKIP Persada Khatulistiwa Sintang, 2022)
The implementation of the 2013 Curriculum proclaims the implementation and realization of character education at all levels of education. One of the character values instilled through thematic learning in elementary schools is tolerance. Daily life in this pluralistic life requires students to have an attitude of tolerance so that they can continue to maintain harmony. The rapid flow of globalization through various media today has eroded many of the values and social attitudes that have become the identity of the nation and begun to be replaced with new values. A holistic learning process that emphasizes developing the value of knowledge, attitudes and skills becomes an appropriate learning model, because the learning process also instills attitudes and skills as a counterweight to knowledge intelligence. The background of this research is the low learning outcomes and lack of tolerance of fourth grade students at SD Negeri 29 Nenak Tembulan. This can be seen from the results of their classical learning mastery, only 47.61% of students succeed in achieving KKM mastery. The purpose of this study is to improve student learning outcomes and tolerance by applying the Value Clarification Technique (VCT) model. The approach in this research is qualitative with descriptive method. The form of the research was classroom action research (CAR), which consisted of two cycles, each cycle involving 21 fourth grade students and one teacher as an observer. The research data was obtained through teacher and student observation, test questions, questionnaires and documentation. There was an increase in learning outcomes and attitudes of tolerance from cycle I to cycle II. Increased cognitive learning outcomes in cycle I with an average mastery of learning outcomes of 71.14% with 66.66% classical completeness and in cycle II 82.21% with 95% classical completeness. Improved affective learning outcomes as measured by a tolerance questionnaire for students in cycle I with an average of 68.14% and cycle II of 76% and psychomotor learning outcomes in cycle I with an average percentage of 67.98% and cycle II with an average percentage 86.5%. Student responses to the application of the Value Clarification Technique (VCT) model showed a positive response. Based on the results of this research, it can be concluded that by applying the Value Clarification Technique (VCT) learning model it can improve learning outcomes and tolerance attitudes of class IV students at SDN 29 Nenak Tembulan in the 2021/2022 academic year.Keywords : Value Clarification Technique, Learning Outcomes, ToleranceÂ Â